A descriptive and interpretive theory of ethical responsibility in public health nursing - Clancy, Anne (Nursing ethics, 2025)
This article presents a descriptive, interpretive theory of ethical responsibility in public health nursing. The theory is based on qualitative empirical studies, a purposeful literature review and meta-ethnography of public health nurses’ experiences of ethical responsibility, interpreted within a philosophical framework. Levianasian philosophy provides the main direction for the authors’ interpretations. The path for theory development consists of three phases: an inspirational phase, an explorative phase and the third phase ‘joining the dots’. The theory illustrates that ethical responsibility in public health nursing is related to the life existentials of temporality and human relationships. Due to blurred boundaries in these essential life structures, public health nurses can experience a sense of satisfaction but also worries, uncertainties and loneliness. The study reveals paradoxical connections between fear and courage, and between freedom, autonomy and a sense of entrapment in responsible relationships. The authors purport that the results of this study are relevant for education and practice and can provide direction for further studies on developing theories of ethical responsibility in other nursing specialities.